Effect of Ca2+ Chelation on the Platelet Inhibitory Ability of the GPIIb/IIIa Antagonists Abciximab, Eptifibatide and Tirofiban - Marciniak, Stanley J.; Jordan, Robert E.; Mascelli, Mary A. (Thrombosis and Haemostasis, 2001)
Objective. Enhanced GPIIb/IIIa binding and inhibition of platelet aggregation of eptifibatide by the reduction of ionized plasma calcium concentrations have been reported. The present study compared the importance of Ca2+ chelation on the in vitro platelet inhibitory profiles of the GPIIb/IIIa antagonists abciximab, eptifibatide and tirofiban. Methods and Results. Turbidimetric platelet aggregation dose response curves of the various GPIIb/IIIa antagonists were performed using platelet rich plasma (PRP) anticoagulated with either trisodium citrate, or the non-chelating anticoagulant, PPACK. The concentrations of antagonist that resulted in 50% inhibition of TRAP-induced (10 M) platelet aggregation (IC50) were measured in the presence of either citrate or PPACK. In addition, the influence of Ca2+ chelation on the binding properties (relative affinity, on- and off-rates) of abciximab for the GPIIb/IIIa receptor on platelets was measured. For all three agonists, the IC50 concentrations were lower for platelets treated with citrate than PPACK, but the degree of difference varied among the agents. The mean TRAP IC50 values for citrate and PPACK were 88.2 ± 12.2 nM and 126.1 ± 28.4 nM for abciximab (1.4 fold enhancement; p = 0.0007), 75.9 ± 13.3 nM and 142.6 ± 32.6 nM for tirofiban (1.9-fold enhancement; p = 0.001), and 260.2 ± 62.5 nM and 810.3 ± 182.5 nM for eptifibatide (3.1-fold enhancement; p = 0.001). A similar shift in effective inhibitor concentrations for abciximab was observed with ADP (10 M). The relative affinities (EC50), on- and off-rates of abciximab for the platelet GPIIb/IIIa receptor in the presence of trisodium citrate and PPACK were equivalent. Conclusions. These data confirm previous observations that Ca2+ chelation afforded by citrate decreases the effective inhibitor concentrations of GPIIb/IIIa antagonists, as assessed by turbidimetric platelet aggregation. However, the extent of decrease was less for abciximab and tirofiban, compared to eptifibatide.
Keywords: Platelet aggregation; anticoagulants; GPIIb/IIIa antagonists; Ca2+ chelation